IMPACT OF CLIMATE CHANGE ON THE POTENTIAL DISTRIBUTION OF NATIVE AND INVASIVE GRASSES IN THE CERRADO - Oliveira, Paula Alves; de Moura, Cristiane Coelho; Santos, Lidia Gabriella; Pereira, Israel Marinho; Bueno, Marcelo Leandro; Machado, Evandro Luiz Mendonça (Floresta, 2020)
Biological invasion, mainly by African grasses, is one of the main threats to the Cerrado's biodiversity. The objective of this study was to elucidate the distribution patterns of the exotic grass Melinis minutiflora and the native grass Trichanthecium cyanescens, in order to verify the areas of potential occurrence of these species and, thus, to infer if their potential distribution will be affected by climate changes. Species occurrence data and ten uncorrelated climatic variables referring to the forecasts for the current period and future forecasts (2050 and 2070) were used for the analysis of the modeling. The models indicated the existence of environmental suitability, with AUCs above 0.8 (good) being observed in M. minutiflora and above 0.9 (excellent) in T. cyanescens. It is concluded that climate change may have negative impacts on the geographic distribution of these species, reducing the area of environmental suitability for them. In addition, the species studied have similar areas of potential distribution and regularly overlap, which can make M. minutiflora a threat to the conservation of T. cyanences, due to the invasion potential of the first.